Friuli food and wine : Frasca cooking from Northern Italy's mountains, vineyards, and seaside - Stuckey, Bobby; Mackinnon-Patterson, Lachlan; Erickson, Meredith, 1980- (Ten Speed Press, 2020)
"Bordered by Austria, Slovenia, and the Adriatic Sea, the northeastern Italian region of Friuli Venezia Giulia is an area of immense cultural blending, geographical diversity, and idyllic beauty. This tiny sliver of land is home to one of the most refined food and wine cultures in the world and yet remains off the grid. The unique cuisine of Friuli is what inspires the menu at Frasca, a James Beard Award-winning restaurant in Boulder, CO, helmed by master sommelier Bobby Stuckey and chef Lachlan Mackinnon-Patterson. Meaning "branch" or "bough", the word frasca refers to the Friulian tradition of hanging a branch outside the family farm as a sign that you had new wine to sell. Frasca celebrates this practice and the wine and cuisine of Friuli through 80 recipes and wine pairings. Dishes such as Gnocchi with Quail Ragu and Thyme, Branzino Crudo with Herbs, and Friulano Bean Soup with Braised Pork Shoulder are organized by The Land, The Sea, and The Mountains, while profiles of local winemakers and wines, including Tocai, Ribolla Gialla, Malvasia Istriana, and Verduzzo, open up new pairing possibilities. Showcasing the best Friulian wines you can buy outside of Italy as well as restaurant and winery recommendations, this beautifully photographed cookbook, wine guide, and travelogue brings the delicious secrets of this untouched part of Italy into your home kitchen"--